Potential of UAV-Generated Orthophotos in Assessing Environmental Vulnerability to Landslides in Ngasinan Village, Purworejo Regency, Central Java - Astuti, Yeni; Sartohadi, Junun; Samodra, Guruh (Faculty of Geography, Universitas Gadjah Mada, 2025)
Ngasinan Village in Bener District, Purworejo Regency, has mountainous and sloping topography, which increases the risk of landslides. However, there is currently no available information regarding the village's environmental vulnerability to landslides, which is essential for disaster mitigation planning. This study aims to assess the environmental vulnerability to landslides in Ngasinan Village using orthophotos as an alternative to a census. The primary data used in this research include aerial photographs taken by an unmanned aerial vehicle (UAV) and Ground Control Points (GCPs) to ensure the accuracy of the orthophotos. The vulnerability parameters analyzed include socio-economic and physical environmental aspects. Aerial photo interpretation was used to identify building structures, the type of predominant walls, building age, building area, electricity usage, and distance from proper roads. The Digital Terrain Model (DTM) was used to extract parameters such as topographic clusters, topographic elevation, distance to steep slopes, and distance to very steep slopes. Environmental vulnerability analysis was conducted using interview data and questionnaires from research samples. The results show that Ngasinan Village falls into the medium vulnerability class. Orthophotos proved to be an accurate data source for assessing environmental vulnerability to landslides, with an accuracy rate of 86.66%. Furthermore, information on the vulnerability of houses to landslides can be obtained more easily and quickly through observation and interpretation of orthophotos compared to the census method. Received: 2023-03-29 Revised: 2023-07-31 Accepted: 2025-06-05 Published: 2025-06-16